Attitude and perception versus reality of COVID-19 vaccination among healthcare professional: a survey - Deodhar, Divya; Kumar, J. Vignesh; E. Paul, Hema; J. Rajan, Sudha; Murugesan, Malathi; Rupali, Priscilla (International Journal of Research in Medical Sciences, 2023)
Background: The pandemic of COVID-19 infection has almost paralyzed the world since the first infection was reported in December 2019. We have seen 3 waves of infection in the country, out of which the second wave caused by the delta variant was the most severe. Along with the preventive measures of masking, maintaining social distance, and handwashing, the vaccines seemed to be the most logical next step. Many vaccines received emergency use approvals with hardly any efficacy and adverse effects data available with the process inducing a significant amount of anxiety among the public. This survey was aimed at understanding the attitude and perception of our hospital employees towards COVID-19 vaccination. Methods: This is a cross-sectional study conducted among health care workers (HCW) at CMC, Vellore between March 2021 to July 2021. The HCWs who are willing to participate in this study were recruited and collected the quantitative data on their attitude and perception towards COVID vaccine. In-depth interviews were conducted among those who did not take vaccine to understand the reasons for not taking vaccine. The data were analyzed using statistical package for the social sciences (SPSS). Results: The survey results were analyzed on 435 HCWs. 58.4 percent of the HCWs trust the institutional protocols as the trusted source of information about vaccine. Most of the HCWs agreed that vaccines are the only protective way, and they are safe and effective. Conclusions: Sensitization and awareness programs with transparency of vaccine development processes, safety and efficacy will help remove barriers.